2013
DOI: 10.1515/cclm-2013-0200
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of cystic fibrosis: an experience of 181 cases

Abstract: PD for CF should be performed in reference laboratories equipped for gene scanning and linkage analysis, with a multidisciplinary staff able to offer counselling to couples during all phases of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Furthermore, in six cases STR preliminary analysis revealed that CV DNA was contaminated by maternal DNA; they included one case of haemophilia (in which the foetus was female), two cases of thalassaemia (in which the paternal mutation was absent) and three cases for which PD was not concluded. In all other cases, including eight twin dichorionic pregnancies, PD was concluded [see also [12][13][14][15]. Finally, in 15 cases, STR analysis revealed non-paternity.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, in six cases STR preliminary analysis revealed that CV DNA was contaminated by maternal DNA; they included one case of haemophilia (in which the foetus was female), two cases of thalassaemia (in which the paternal mutation was absent) and three cases for which PD was not concluded. In all other cases, including eight twin dichorionic pregnancies, PD was concluded [see also [12][13][14][15]. Finally, in 15 cases, STR analysis revealed non-paternity.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, the laboratory must be equipped with adequate quality control programmes [30]. For most diseases we used two different analytical procedures (that have invariably given concordant results), including, where available, linkage analysis [12][13][14][15]31]. Finally, the laboratory must be equipped to perform a preliminary analysis of maternal cell contamination and paternity testing (since in most PDs only parental mutations are analysed).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, a positive PD of haemophilia is usually not followed by pregnancy interruption, particularly in countries that offer an adequate quality of patient care [16,17]. In fact, in our series 30% of positive PDs for haemophilia were not followed by pregnancy interruption, differently, in our experience, from cystic fibrosis [18], Duchenne muscular dystrophy, myotonic dystrophy type 1 [19], thalassaemia [20] and other severe diseases [9] for which pregnancy interruption was planned in more than 95% of positive PD. Of course, the multidisciplinary team of counsellors must be aware of all the novel therapies available for haemophilic patients and must give the same support to all couples irrespective of the family's decision [21].…”
Section: Discussionmentioning
confidence: 57%